Ball-milling-induced amorphization of zeolitic imidazolate frameworks (ZIFs) for the irreversible trapping of iodine. - Bennett, T; Saines, P; Keen, D; Tan, J; Cheetham, A (2013)
The I2-sorption and -retention properties of several existing zeolitic imidazolate frameworks (ZIF-4, -8, -69) and a novel framework, ZIF-mnIm ([Zn(mnIm)2 ]; mnIm=4-methyl-5-nitroimidazolate), have been characterised using microanalysis, thermogravimetric analysis and X-ray diffraction. The topologically identical ZIF-8 ([Zn(mIm)2]; mIm=2-methylimidazolate) and ZIF-mnIm display similar sorption abilities, though strikingly different guest-retention behaviour upon heating. We discover that this guest retention is greatly enhanced upon facile amorphisation by ball milling, particularly in the case of ZIF-mnIm, for which I2 loss is retarded by as much as 200 °C. It is anticipated that this general approach should be applicable to the wide range of available metal-organic framework-type materials for the permanent storage of harmful guest species.